A-type potassium channels expressed from Shaker locus cDNA. - Iverson, L E (1988)
A-type K+ currents are expressed in Xenopus oocytes injected with in vitro-synthesized transcripts from cDNAs for the Drosophila Shaker (Sh) locus. A single Sh gene product, possibly as a multimer, is sufficient for formation of functional A channels. Various Sh RNAs express A currents with distinct kinetic properties. An analysis of structure-function relationships shows that the conserved central region of Sh polypeptides determines ionic selectivity and overall channel behavior, whereas the divergent amino and carboxyl termini can modify channel kinetics. Alternative splicing of Sh gene transcripts may provide one mechanism for the generation of K+ channel diversity.